Urban space at the time of the war. Configuration and visual image of Kharkiv (Ukraine) - Cutini, Valerio; Averbakh, Mykhaylo; Demydiuk, Oksana (TeMA - Journal of Land Use, Mobility and Environment, 2023)
This paper is devoted to consider the changes in the surrounding artificially created environment under the influence of the tragic circumstances of the Russian military invasion in Ukraine and the peculiarities in the perception of the urban environment, resulting from the interaction between it and the people. The war has changed the usual visual image of Ukrainian cities: many cities suffer from shelling, many objects of architectural and cultural value have been destroyed. The ruins of Mariupol, Kharkiv, Mykolaiv, Izium will represent the new view of these cities for a long time, as a reminder of the terrible events and suffering of individuals and communities. A lot of visual-informational forms have appeared, accompanying on the mental, content and emotional levels the resistance of Ukrainians. Visual forms capturing the destruction of streets and houses, household activities, suffering and pain of residents are shown focusing on the case study of Kharkiv, whose inner geography is considered within a configurational framework. The article, written under the storm that is still ravaging Ukraine, also displays a variety of “pictures” of people’s living in the Kharkiv metro, whose intended use is transformed into a shelter. Fragments and knowledge elements that ought to be recollected and put together while discussing strategies and choices for reconstructing Kharkiv when the weapons are finally laid down.